1992
DOI: 10.1002/ajmg.1320420519
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the origin of ring/marker chromosomes in patients with ullrich‐turner syndrome using X and Y specific alpha satellite DNA probes

Abstract: Fluorescent in situ hybridization (FISH) using X and Y chromosome-specific alpha satellite DNA probes hybridizing to loci DXZ1 and DYZ3 was performed to identify the origin of ring/marker chromosomes in 6 patients with Ullrich-Turner syndrome (UTS). All patients had a mosaic karyotype, 5 with 45,X/46,X,r(?) and one with 45,X/46,X,mar. We demonstrated that the marker/ring chromosome in each of these 6 patients originated from the X. A timely knowledge of the X or Y origin of ring and marker chromosomes can be c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1992
1992
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…Although an association of ring (X) with mental retardation has been previously reported in UllrichTurner syndrome [Kushnick et al, 1987;Grompe et al, 1992;Van Dyke et al, 1992], our present review found several cases with a ring(X) that were associated with a typical Ullrich-Turner syndrome phenotype but lacked mental retardation [Crolla and Llerena, 1988;Koch et al, 1990;Cooper et al, 1991;Lindgren et al, 1992;Tharapel et al, 1992;Zenger-Hain et al, 1993;Gonzales-del Angel et al, 1995]. More recent evidence indicates that patients with a small ring X-chromosome lacking the XIST gene escape inactivation and are at increased risk for mental retardation [Migeon et al, 1993;Wolff et al, 1994;Jani et al, 1995].…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…Although an association of ring (X) with mental retardation has been previously reported in UllrichTurner syndrome [Kushnick et al, 1987;Grompe et al, 1992;Van Dyke et al, 1992], our present review found several cases with a ring(X) that were associated with a typical Ullrich-Turner syndrome phenotype but lacked mental retardation [Crolla and Llerena, 1988;Koch et al, 1990;Cooper et al, 1991;Lindgren et al, 1992;Tharapel et al, 1992;Zenger-Hain et al, 1993;Gonzales-del Angel et al, 1995]. More recent evidence indicates that patients with a small ring X-chromosome lacking the XIST gene escape inactivation and are at increased risk for mental retardation [Migeon et al, 1993;Wolff et al, 1994;Jani et al, 1995].…”
Section: Discussionmentioning
confidence: 45%
“…Including the present 23 cases, a total of 86 sex chromosome markers studied with FISH have been reported Crolla and Learna, 1988;Kozma et al, 1988;Crolla et al, 1989;Babu et al, 1990;Cole et al, 1990;Guttenbach et al, 1990;Koch et al, 1990;Lin et al, 1990;Cooper et al, 1991;Pohlschmidt et al, 1991;Bajalica et al, 1992;Bernstein et al, 1992;Hou et al, 1992;Lindgren et al, 1992;Qu et al, 1992;Tharapel et al, 1992;Van Dyke et al, 1992;Dennis et al, 1993;Duncan et al, 1993;Pezzolo et al, 1993;Rajangam et al, 1993;Zenger-Hain et al, 1993; Cole et al, 1994;Daniel et al, 1994;Macera et al, 1994;Robson et al, 1994;Slim et al, 1994;Amiel et al, 1995;Callén et al, 1995;Cantú et al, 1995;Gonzalesdel Angel et al, 1995;Silahtaroglu et al, 1995]. These cases can be subdivided into four ascertainment groups: 1) Ullrich-Turner syndrome without mental retardation, 2) Ullrich-Turner syndrome with mental retardation, 3) prenatally diagnosed cases, and 4) other cases.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…As compared with microdeletions of Yq11, gross structural abnormalities of Y chromosome occur much less commonly in infertile men [Yoshida et al, 1997]. In the literature, most cases carrying gross structurally abnormal Y chromosomes were referred because of features of Turner syndrome or ambiguous genitalia [Diekmann et al, 1992;Tharapel et al, 1992;Henegariu et al, 1997]. Herein, we describe detailed molecular characterization of two azoospermic men with r (Y).…”
Section: Introductionmentioning
confidence: 92%
“…For this comparison, we reviewed findings for 85 cases reported in the medical literature from 1980-2002 [Dallapiccola et al, 1980;Berkovitz et al, 1983;Kushnick et al, 1987;Koch et al, 1990;Lin et al, 1990;Guttenbach et al, 1991;Johnson et al, 1991;Grompe et al, 1992;Lindgren et al, 1992;Tharapel et al, 1992;Van Dyke et al, 1992;Dennis et al, 1993;Cole et al, 1994;Collins et al, 1994;Wolff et al, 1994;Cantu et al, 1995;Blumenthal and Allanson, 1997;El Abd et al, 1997;McGinniss et al, 1997;Uehara et al, 1997;Yorifuji et al, 1998;El Abd et al, 1999;Dennis et al, 2000;Kuntsi et al, 2000;Migeon et al, 2000;Turner et al, 2000;Stankiewicz et al, 2001;Tomkins et al, 2002]. We have presented separately the data from a large study of 47 cases in Table II because 15 of the cases in this study were reported earlier and included in our literature review Kuntsi et al, 2000].…”
Section: Clinical Evaluationmentioning
confidence: 99%